(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Regional anesthesia is commonly used for upper limb surgeries below the elbow because of its effectiveness, safety, and reduced postoperative complications. Axillary brachial plexus block and intravenous regional anaesthesia (IVRA) are widely practiced techniques for such procedures. The present study was conducted to compare the efficacy and safety of these two regional anesthetic techniques. Methodology: This prospective comparative study was conducted in the Department of Anaesthesiology at Sree Mookambika Institute of Medical Sciences from April 2025 to February 2026. A total of 60 patients aged between 18 and 50 years undergoing elective and emergency upper limb surgeries below the elbow were included in the study. Patients were divided into two groups of 30 each. Group I received axillary brachial plexus block using 1% lignocaine with adrenaline, while Group II received intravenous regional anaesthesia using 0.5% lignocaine. Parameters such as onset and duration of analgesia, quality of analgesia, motor blockade, and perioperative complications were assessed and compared. Statistical analysis was performed using Student’s t-test, and a p-value less than 0.05 was considered statistically significant. Results: The onset of analgesia was significantly faster in Group II (3.7 ± 0.9 minutes) compared to Group I (12.8 ± 1.6 minutes) with P < 0.001. Grade I analgesia quality was observed in 76.6% of patients in the IVRA group and 53.3% in the axillary block group. Denser motor blockade and prolonged duration of analgesia were observed in Group I. The mean duration of analgesia was significantly higher in Group I (67.5 ± 4.5 minutes) compared to Group II (46.8 ± 8.8 minutes) with P < 0.001. Conclusion: Both axillary brachial plexus block and intravenous regional anaesthesia were effective techniques for upper limb surgeries below the elbow. IVRA provided rapid onset of analgesia, whereas axillary brachial plexus block offered prolonged postoperative analgesia and superior motor blockade.